PERAN MASYARAKAT DESA DALAM MELESTARIKAN HUTAN DI NEGERI SAUNULU KECAMATAN TEHORU KABUPATEN MALUKU TENGAH - Nova S Tuwael; Jusmy D Putuhena; B B Seipalla (Pattimura University, 2022)
This research was conducted in the State of Saunulu with the aim of knowing the role of the village community in conserving the forest and knowing the factors that influence the role of the village community in conserving the forest. The method used in this study is a qualitative method using descriptive analysis to describe systematically, factually and accurately about the role of village communities in conserving forests. Data collection techniques are interviews, observation, and documentation. The results of the study show the role of the community in preserving forests in the State of Saunulu, namely reforestation, plant maintenance. The factors that influence the role of the village community are rules, taboos, techniques, and traditional traditions. The inhibiting factors are ethics, rules, taboos, and traditions which are all applied by customary leaders, church rules and direct involvement both personally and in groups